Pengembangan Video Pembelajaran Berbasis Powtoon Berorientasi STEM (Science, Technology, Engineering, Mathematics) Terkoneksi Ayat Alqur’an Pada Materi Usaha Dan Energi Kelas X MIPA Di SMA/MA - Hilan Aini Latifah; Sri Maiyena (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2021)
This research is based on the thinking of students who think that learning physics is difficult and the available instructional media are less attractive. As a result, students are not interested in learning. This problem occurs because educators have not taken advantage of existing technology and the lack of variety of educators in making media, so that a solution to this problem is needed, namely a STEM-oriented (Science, Technology, Engineering, Mathematical)-based learning videos connected to the Qur'anic verses on business and energy materials for class X Mathematics and Natural Sciences in SMA/MA. The purpose of this study was to determine the validity and practicality of STEM-oriented (Science, Technology, Engineering, Mathematical)-based learning videos connected to the Qur'anic verses on business and energy materials for class X Mathematics and Natural Sciences in SMA/MA. The development model used in this study is a 4D model (define, design, develop, disseminate) which only uses three stages, namely defining, designing, and developing STEM-oriented (Science, Technology, Engineering, Mathematical)-based learning videos connected to the Qur'an. 'an on the material of work and energy class X MIPA in MA. This learning video will be conducted in a limited trial for students of class X MIPA 1 MAN 2 Tanah Datar to find out the response regarding the practicality of using this learning video which was being developed. From the results of research on the validation aspect of developing STEM-oriented Powtoon-based learning videos connected to the Qur'anic carried out by two validators who are lecturers and one teacher with a percentage of 79.37% (valid criteria). The results of the practicality test of students show a percentage of 85.28% which means it is very practical. For the practicality value of the teacher of 85.29% which shows the meaning that the STEMoriented Powtoon-based learning video is very practical to use by educators in physics learning.